Research on environmental regulation, environmental protection tax, and earnings management - Fu, Shiwen; Yuan, Jianguo; Xiao, Deyun; Chen, Zhiqiang; Yang, Gaorong (Frontiers in Environmental Science, 2023)
Based on the data of heavily polluting enterprises of A-share listed companies in Shanghai and Shenzhen from 2012 to 2018, this paper explores the impact of environmental regulation and environmental tax on enterprise earnings management. We find that environmental regulation promotes the upward real earnings management of enterprises and inhibits the upward profit accrual management of enterprises. The joint action of environmental regulation and environmental tax promotes enterprises' upward profit accrual and real earnings management. There is heterogeneity among different enterprise natures, different enterprise scales, different degrees of marketization, different government environmental protection investment intensity, and disclosure of enterprise environmental protection ideas.